A Practical Guide for the Treatment of Symptomatic Heart Failure with Reduced Ejection Fraction (HFrEF) - N. Reed, Brent; A. Sueta, Carla (Current Cardiology Reviews, 2015)
This review will outline the management of patients with symptomatic systolic heart failure or heart failure with reduced ejection fraction (HFrEF), i.e., those with structural heart disease and previous or current symptoms. Determination of volume status and appropriate diuretic administration is important in heart failure management. Inhibition of the renin-angiotensin-aldosterone and sympathetic nervous systems improves survival and decreases hospitalizations in patients with systolic or reduced ejection fraction HF (HFrEF). Beta blockers and aldosterone antagonists improve ejection fraction. Indications for additional agents including nitrates plus hydralazine, digoxin, statins, omega 3 polyunsaturated fatty acids, anticoagulants, and antiarrhythmics will be discussed. Choice of agents, dose-related effects, strategies to minimize adverse effects, and medications to avoid will be presented.
Keywords: beta blocker